Easing the transition: do Talent Lessons and Talent Talks support students’ self-regulated learning skills in the transition from primary to secondary education? - Beckers, Jorrick; Bolkenbaas, Sandra; Verbree, Anne-Roos; Schils, Trudie; van Gog, Tamara; de Bruin, Anique (Frontiers in Education, 2023)
The transition from primary to secondary school is a period that can affect students negatively, with regular drops in academic achievement observed. Training students' self-regulated learning skills might help prevent some of the negative outcomes associated with the transition. We investigate Talent Talk and Talent Lesson interventions, which aim to improve students' metacognitive and affective self-regulation through enhancement of personal significance and strengthening of taskanalysis skills. The present study researched whether Talents Talks and Talent Lessons can be used to improve students' self-regulated learning skills, motivation, and self-efficacy. We employed a quasi-experimental 2x2 design comparing four groups (total N = 233), who received either Talent Talks or Talent Lessons, both, or neither. Students were tested at three separate moments on absolute monitoring accuracy and self-report measures of self-regulated learning, motivation, and selfefficacy, with the interventions being implemented between the first and second moment. There were no significant differences between conditions at any of the test moments. As such, there is at present no evidence suggesting that Talent Talks and Talent Lessons positively influence self-regulation, self-efficacy, and motivation. Effectiveness of the intervention might be increased if Talent Talks and Talent Lessons are adapted, so that students' reflections about talents are tailored to self-regulation of specific tasks.